The use of method (EGP) to build The optimum shares portfolio Under the two methods Allowing short selling and not allow -An analytical study In the Iraq Stock Exchange - Rabie Hadi, Maitham; Shallal Eakaar, Zainab (Iraqi Journal for Administrative Sciences, 2024)
The study aimed to use simplistic methods to build The optimum portfolio to avoid problems arising To use Markowitz model ,Which represents by the huge number Of EstimationTo complete the Covariance Matrix And its inability to provide any indicative evidence Predict the risk rising Which is the basically In building efficient Limit of hazardous assets . Also aimedMeasuring the performance ofportfolioWhich are builtUnder the two instances to allow and not allow short-selling and stand onPerformance resultsBy using the Sharpe Ratio and compared with the performanceReference to market index . The study was basedOf a sample of companies listedIn the Iraq Stock ExchangeAmounted to (42)Companies from various sectors, The study usedMonthly closing stock prices data and The market index issued for 60 months and for of five years from October 2010 until October 2015 . Using a variety of methods , Statistical tests and financial by using statistical program (EXCEL).The study found a number of conclusionsPerhaps one of most importantPossibility of constructing an optimal portfolio The study found a number of conclusionsPerhaps one of most importantPossibility of constructing an optimal portfolioComparable in performance that returns of the reference portfolio marketOr even to be outdone in terms of Simplify input and procedures built . Therefore, the study recommended , the Investors Necessity adoptIn the Iraq Stock ExchangeA simple method of staging(EGP) to build optimal portfolios given their critical importance to investors On one side .In terms of guaranteed optimization trade-off between risks and returns to Financial market, On the other,and ensuring upgrading of financial market efficiency because of the adoption of subscribers on scientific methods to construct optimal portfolios.